Students’ Perception Regarding to the Use of Role Play Technique in Learning Speaking Skills - Wijaya, Michael; Handayani, Ika; Fargianti, Yusti (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2024)
This study aimed to find out how are the perception of students regarding to the use of role play technique in learning speaking skills and also what are strengths and weaknesses of it according to students’ perception at SMP Negeri 1 Kelapa Dua, Tangerang. The research employed a case study method. The data were collected by observation, questionnaire, and interview. The results of the research showed that role play helped students in English vocabulary, English grammar, English comprehension, English pronunciation, and also their English fluency. Moreover, it was more fun and helped them to cultivate their knowledge, made them interested and more enthusiastic, more optimistic, more motivated, taught them about teamwork, involved them directly, and more active. It is proven to be an efficient technique in teaching and learning speaking skills, but less effective in fostering students’ self-confidence. Therefore, it still made them shy and afraid when playing roles.